Dr M launches book - New Sunday Times, , (New Sunday Times, 2014)
KUALA LUMPUR: Former prime minister Tun Dr Mahathir Mohamad launched The Politics of Bangsa Malaysia: Nation Building In a Multiethnic Society at a hotel here yesterday.